Russian students’ life plans: gender and other differences in the estimates of prospects in the labor market - N P Narbut; I V Trotsuk (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2014)
The article summarizes the results of the survey conducted on a sample of students of the Peoples’ Friendship University of Russia to test the questionnaire developed for the operationalization of the youth expectations and concerns in the professional sphere. Previously (1) we described the general features of students’ worldview considering labor market and career plans, in particular the striking combination of quite diverse reasons such as evaluation of the PFUR prestige and image together with very thoughtful and idealistic considerations. This time we focused on factors determining differences in students’ estimates of the situation on the labor market, their commitment to the ideals of personal achievements, perception of studying and requirements of employers, the confidence that they can find a job easily and quickly and fears to become an unemployed, lonely and poor person. The data of national surveys in recent decades show that the Russian society manifests itself as a stereotypical and traditional one in gender questions, especially when it comes to the positions of men and women in the labor market, thus the authors focus on gender differences in students’ responses to the survey questions, but mention other significant distinctions as well.